Exploring Teachers' and Students' Perceptions of Differentiated Instruction in Merdeka Curriculum EFL Classes - Ikhlasul Hamzah; La Sunra; Abdul Halim (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Differentiated Instruction (DI) is central to the Merdeka Curriculum's student-centered framework in Indonesia. Despite theoretical support, its practical implementation, particularly in English as a Foreign Language (EFL) classes, remains inconsistent. This qualitative case study investigates both teachers' and students' perceptions of DI in EFL classes at SMK Negeri 4 Makassar. Data were collected through interviews, observations, and documentation, and analyzed using thematic analysis. Findings reveal that teachers possess intuitive but limited understanding of DI, with partial and situational implementation. Institutional support was reported as general and inadequate, and barriers such as large class sizes and lack of resources hinder effective DI application. Students perceived the learning experience as uniform and lacking in differentiation by learning style or interest. Although supportive teacher behavior was noted, DI aspects such as content, process, product, and environment differentiation were not comprehensively applied. The study concludes with recommendations for enhanced training, infrastructure, and strategic planning to better align DI with Merdeka Curriculum goals.